The law and control of violent video games in Malaysia / Sharifah Nurashiqin Syed Alwi…[et al.] - Syed Alwi, Sharifah Nurashiqin; Mohd Yusof, Hetty Munira; Addnin, Nurul Aimuni; Azizan, Mohd Ramzi (Faculty of Law, 2009)
Video game invention had caused concern due to the violent acts and sensitive issues that are contain in the video game. This has been proven by recent studies that showed the link between video games and violent acts. This is because exposure to violent games had causes a lot of negative effects through player's emotions, thoughts and increases aggressive emotions. Thus, this research is done for the purpose of examining the approach taken by foreign countries in controlling violent video games. In the foreign countries, a specific organizations was established that was responsible to take control the distributions of violent video game. This is in contrast in Malaysia approach when there is no specific law or organization to control the distribution of the violent video game. Thus, in this research various types of methods are use to collect the information that include qualitative type of research, library based research and also retrieving information via internet in order to ascertain measures needed to apply in Malaysia.